Secreted hepatitis B virus splice variants differ by HBV genotype and across phases of chronic hepatitis B infection. Issue 8 (28th May 2022) - Maslac, Olivia; Wagner, Josef; Sozzi, Vitina; Mason, Hugh; Svarovskaia, Jenny; Tan, Susanna; Gaggar, Anuj; Locarnini, Stephen; Yuen, Lilly; Littlejohn, Margaret; Revill, Peter A.
Abstract: Chronic hepatitis B (CHB) is characterized by progression through different phases of hepatitis B virus (HBV) infection and disease. Although not necessary for HBV replication, there is increasing evidence that HBV splice variants are associated with liver disease progression and pathogenesis. However, there have been no studies till date on the frequency or diversity of splice variants for different HBV genotypes across the phases of CHB. Next generation sequencing data from 404 patient samples of HBV genotype A, B, C or D in Phase I, Phase II or Phase IV of CHB was analysed for HBV splice variants using an in house bioinformatics pipeline. HBV splice variants differed in frequency and type by genotype and phase of natural history. Splice variant Sp1 was the most frequently detected (206/404, 51% of patients), followed by Sp13 (151/404 37% of patients). The frequency of variants was generally highest in Phase II (123/165, 75% of patients), a phase typically associated with enhanced immune activation, followed by Phase I (69/99, 70% of patients). Splice variants were associated with reduced hepatitis B e antigen (HBeAg) levels and statistically reduced likelihood of achieving HBsAg loss (functional cure) in Phase II patients for Sp1 and Sp13 ( p  = .0014 and .0156, respectively). The frequency of HBV splice variants in patient serum differed markedly by HBV genotype and phase of CHB natural history. The increased levels of HBV splice variants detected in CHB phase II patients compared with the higher replicative Phase I in particular warrants further investigation.